2000
DOI: 10.1530/eje.0.1430755
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of combined technetium-99m-sestamibi scintigraphy and high-resolution ultrasonography in parathyroid localization: comparative study in 91 patients with primary hyperparathyroidism

Abstract: Objective: To evaluate the usefulness of the combination of 99m Tc-sestamibi/ 99m Tc-pertechnetate subtraction scintigraphy (SS) and high-resolution neck ultrasonography (US) in patients with primary hyperparathyroidism (pHPT) undergoing parathyroidectomy. Design and Methods: Ninety-one patients with proved pHPT were studied, excluding patients with persistent or recurrent disease. There were 65 (71.4%) women and 26 (28.6%) men, with a median age of 59 years (range 18±78 years). All patients underwent both SS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
68
1
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 40 publications
12
68
1
8
Order By: Relevance
“…The results of the statistical analysis of data from group C confirm the findings of numerous other studies [29][30][31][32], that is that preoperative use of ultrasound and scintigraphy in parallel improves accuracy in the detection and localization of single pathological parathyroid glands In fact, the use of both methods was associated with higher diagnostic sensitivity (87 %) than use of ultrasound (71 %) or scintigraphy (73 %) alone. We nonetheless feel that, as reported in previous studies, the inferior sensitivity of ultrasonography observed in Group C is due to the absence of dedicated physician sonographers and/or to the relative lack of experience of some of the examiners.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the statistical analysis of data from group C confirm the findings of numerous other studies [29][30][31][32], that is that preoperative use of ultrasound and scintigraphy in parallel improves accuracy in the detection and localization of single pathological parathyroid glands In fact, the use of both methods was associated with higher diagnostic sensitivity (87 %) than use of ultrasound (71 %) or scintigraphy (73 %) alone. We nonetheless feel that, as reported in previous studies, the inferior sensitivity of ultrasonography observed in Group C is due to the absence of dedicated physician sonographers and/or to the relative lack of experience of some of the examiners.…”
Section: Discussionsupporting
confidence: 83%
“…Of these, USG, Tc-99m scintigraphy, and CT are the most commonly used methods [5]. On USG, a parathyroid adenoma typically appears hypoechoic, oval-shaped, and homogenous.…”
Section: Preoperative Evaluation Of Parathyroid Pathologymentioning
confidence: 99%
“…Fourdimensional computed tomography (4D-CT) is the most advanced of CT [6]. MIBI together with USG has a diagnostic sensitivity of 95% and is the most frequently used of the methods described above [5]. CT, PET, and selective venous sampling are rarely used in the reported literature.…”
Section: Preoperative Evaluation Of Parathyroid Pathologymentioning
confidence: 99%
“…(Dimashkieh) Individually, sestamibi and US studies have limited accuracy, but the use of both imaging modalities increases the ability to successfully identify a single adenoma: the reported combined sensitivity is 95%. (Lumachi, 2000) When the results of both the sestamibi and US studies are concordant, the accuracy for identifying a single adenoma can be as high as 98%. (Haciyanli) Pros Cons…”
Section: Ultrasound (Us) Scansmentioning
confidence: 99%
“…(Lumachi, 2000) It is also recommended for patients with familial PHPT; patients with multiple endocrine neoplasia syndrome type I and IIA; and patients who may have a carcinoma. In addition, it should be performed when a thyroid resection is planned concomitantly.…”
Section: Indicationsmentioning
confidence: 99%